RNA-seq Analysis of the BCG Vaccine in a Humanized Mouse Model - Jie Wang; Jie Mi; Yan Liang; Xueqiong Wu; Junxian Zhang; Yinping Liu; Lan Wang; Yong Xue; Yingchang Shi; Wenping Gong; Xinru Wang (Zoonoses, 2023)
This study was aimed at screening differentially expressed genes (DEGs) and exploring the potential immune mechanism induced by the Bacillus Calmette-Guerin (BCG) vaccine in a humanized mouse model. Candidate DEGs between mice vaccinated with BCG or injected with PBS were identified through transcriptomics, and their biological functions, signaling pathways, and protein interaction networks were analyzed through bioinformatics. A total of 1035 DEGs were identified by transcriptomics: 398 up-regulated and 637 down-regulated. GO analysis indicated that these DEGs were significantly enriched in cell adhesion, oxygen transport, receptor complex, carbohydrate binding, serine-type endopeptidase activity, and peroxidase activity terms. KEGG analysis indicated that these DEGs were involved in the Rap1 signaling pathway, axon guidance, PI3K-Akt signaling pathway, natural killer cell mediated cytotoxicity, and cytokine-cytokine receptor interaction. Protein interaction network analysis demonstrated that the Myc, Vegfa, and Itgb3 proteins had the highest aggregation degree, aggregation coefficient, and connectivity. The BCG vaccine induced 1035 DEGs in humanized mice. Among them, the differentially expressed down-regulated genes myc and itgb3 involved in the PI3K-Akt signaling pathway may play essential roles in the immune mechanism of the BCG vaccine.